PKM Pelatihan Pembuatan Sinom Belimbing Wuluh bagi Masyarakat Desa - Luluk Firdausiyah; Fenni Yuniasari; Umi Salamah; Erna Nikmatul Indah; Khoirul Anam (Al-Qalam Institute, 2023)
This research focuses on evaluating the effectiveness of entrepreneurship training related to making sinom starfruit drinks in Tempuran Village, Pungging District, Mojokerto Regency. The scope of the study includes identification of economic problems, application of learning approaches, as well as evaluation of the social and economic impact of this training activity. The aim of this research is to evaluate the extent to which entrepreneurship training can diversify sources of income, especially among women in Tempuran Village, by focusing on production Sinom starfruit drink. The method used is a quantitative approach through a pre-post experimental method (pre-posttest experiment). Data were collected before and after training to analyze changes in family income. The research results showed that the training activities made a significant contribution in increasing the knowledge and skills of the Tempuran Village community regarding making sinom starfruit drinks. This activity is expected to provide new opportunities in empowering the local community's economy, enabling them to develop businesses based on local products.